Investigating the effects of the plaC accessory protein on disulphide bond formation in plantaricin 423 heterologously expressed in escherichia coli - Joos, Carla Grete (Stellenbosch : Stellenbosch University, 2024)
Thesis (MSc)--Stellenbosch University, 2024.